1095 Use Of Mobile Devices At Night Associated With Mental Health In Young Adults. (27th May 2020) - Mason, B; Tubbs, A; Hale, L; Branas, C; Barrett, M; Killgore, W D; Wills, C C; Grandner, M A
Abstract: Introduction: Mobile technology use in bed is becoming commonplace and associated with habitual short sleep duration. The present study examined whether device use at night was related to mental health. Methods: Data from the Sleep and Healthy Activity, Diet, Environment, and Socialization (SHADES) study comes from a community-based sample, which was restricted to N=473 between the ages of 22-29. Device use was assessed as presence in the room at night, any use at night, texting, emailing, browsing the internet, making or receiving calls, and using social media. Participants were also asked how often they are woken by a call/alert from their phone (unplanned), how often they are woken by their phone alarm (planned), and how often they check their phone at night. These were recorded as never, rarely, some nights, almost every night, and every night, and were assessed as an ordinal outcome. Predictors included score on the Patient Health Questionnaire depression scale (PHQ9), GAD7 anxiety scale, Perceived Stress Scale (PSS), and Multidimensional Scale of Perceived Social Support (MSPSS). Ordinal logistic regression analyses were adjusted for age, sex, race/ethnicity, education, and income. Results: Depression was associated with texting (oOR=1.03, p=0.025), email (oOR=1.03, p=0.022), internet (oOR=1.05, p=0.003), unplanned awakenings (oOR=1.05, p=0.001), and checking the phone (oOR=1.09, p<0.0005). Anxiety was associated with texting (oOR=1.05, p=0.001), email (oOR=1.05, p=0.001), internet (oOR=1.05, p=0.002), social media (oOR=1.04, p=0.009), unplanned awakenings (oOR=1.06, p<0.0005), planned awakenings (oOR=1.04, p=0.025), and checking the phone (oOR=1.10, p<0.0005). Perceived stress was associated with internet (oOR=1.02, p=0.034), unplanned awakenings (oOR=1.02, p=0.045), and checking (oOR=1.04, p<0.0005). Social support was associated with decreased checking (oOR=0.98, p=0.018). Conclusion: Mobile device use at night itself is not associated with mental health, but specific activities may be. Also, those who report more disruptions from the device and more checking of the device also report worse mental health. Relationships might be bidirectional. Support: Dr. Grandner is supported by R01MD011600 The SHADES study was funded by R21ES022931